The sponsor effect how to be a better leader by investing in others - Sylvia Ann Hewlet (Boston, Massachusetts Harvard Business Review Press, 2019)
Who's delivering for you? Who has your back? Who's burnishing your brand and expanding what you can get done in this world? Sponsorship is a two-way alliance where a leader partners with junior talent to build their skills and advocate for their promotion--all while receiving stellar performance and loyalty in return. Many know the benefit of finding a sponsor: men and women with sponsors are much more likely to progress to the next rung in their careers than those without. But according to author Sylvia Ann Hewlett, being a sponsor is just as important to career growth as finding one. Senior executives who proactively sponsor others are 53 percent more likely to receive a promotion--and middle-level managers who have proteges are 60 percent more likely to receive a stretch assignment--than those who don't.-- Provided by publisher
Includes bibliographical references and index
Keywords: Mentoring in business